Correlation Of Linear Measurements Of Spleen With Splenic Volume in Computed Tomography - Suwal , S; Subedi , K; Gurung , G (Journal of Institute of Medicine Nepal, 2018)
Introduction: The purpose of this study was to assess the normal linear measurements of spleen in Nepalese adults by Computed Tomography (CT) and their correlation with splenic volume.Methods: This was a prospective cross sectional observational study done in 264 peoples undergoing abdominal CT examination for various clinical indications not pertaining to spleen, in Department of Radiology & Imaging, Tribhuvan University Teaching Hospital (TUTH). Four linear measurements of spleen were obtained in axial plane. Craniocaudal length of the spleen was also obtained. The volume was obtained by adding cross-sectional area of spleen from 10 mm contiguous axial images and multiplying them with the slice thickness. The relationships between various linear measurements of spleen with spleenic volume were derived.Results: The mean length of spleen along long axis was 9.3 +/- 1.3 cm, and the mean length along the craniocaudal axis was 7.6 +/- 1.5 cm. The mean width, maximum thickness, and thickness at hilum of the spleen were 9.3 +/- 1.7 cm, 5.1 +/- 1.2 and 3.2 +/- 0.6 cm respectively. The mean splenic volume was 151.20 cm3 ±  59.62 cm3. Significant positive correlations were noted between linear measurements and volume, the strongest being the width followed by the craniocaudal length.Conclusion: Linear measurements of the spleen in CT show strong correlation with volume and hence can replace the splenic volume measurements while defining splenomegaly